Conversion to stem‐cell state in response to microenvironmental cues is regulated by balance between epithelial and mesenchymal features in lung cancer cells. Issue 2 (22nd October 2015) - Andriani, Francesca; Bertolini, Giulia; Facchinetti, Federica; Baldoli, Erika; Moro, Massimo; Casalini, Patrizia; Caserini, Roberto; Milione, Massimo; Leone, Giorgia; Pelosi, Giuseppe; Pastorino, Ugo; Sozzi, Gabriella; et al.
Abstract : Cancer cells within a tumor are functionally heterogeneous and specific subpopulations, defined as cancer initiating cells (CICs), are endowed with higher tumor forming potential. The CIC state, however, is not hierarchically stable and conversion of non‐CICs to CICs under microenvironment signals might represent a determinant of tumor aggressiveness. How plasticity is regulated at the cellular level is however poorly understood. To identify determinants of plasticity in lung cancer we exposed eight different cell lines to TGFβ1 to induce EMT and stimulate modulation of CD133+ CICs. We show that response to TGFβ1 treatment is heterogeneous with some cells readily switching to stem cell state (1.5–2 fold CICs increase) and others being unresponsive to stimulation. This response is unrelated to original CICs content or extent of EMT engagement but is tightly dependent on balance between epithelial and mesenchymal features as measured by the ratio of expression of CDH1 (E‐cadherin) to SNAI2. Epigenetic modulation of this balance can restore sensitivity of unresponsive models to microenvironmental stimuli, including those elicited by cancer‐associated fibroblasts both in vitro and in vivo. In particular, tumors with increased prevalence of cells with features of partial EMT (hybrid epithelial/mesenchymal phenotype) are endowed with the highest plasticity and specific patterns of expression of SNAI2 and CDH1 markers identify a subset of tumors with worse prognosis. In conclusion, here we describe a connection between a hybrid epithelial/mesenchymal phenotype and conversion to stem‐cell state in response to external stimuli. These findings have implications for current endeavors to identify tumors with increased plasticity. Highlights: Signals from the microenvironment are involved in modulation of cancer initiating cells (CICs) in lung cancer. Balance between epithelial/mesenchymal features is a crucial determinant of proclivity to stemness phenotype acquisition. Epigenetic modification of epithelial/mesenchymal balance can regulate response to microenvironmental stimuli. A specific pattern of expression of E‐cadherin and SNAI2 is associated with worst prognosis in NSCLC.